Essential User Experience Principles for Programming-Oriented Role-Playing Games: An Expert-Validated Thematic Synthesis - Panji Rachmat Setiawan; Maizatul Hayati Mohamad Yatim (SISTEMASI, 2026)
This study aims to identify and validate the essential User Experience (UX) principles for the design of programming-oriented Role-Playing Games (RPG), a subgenre that requires players to navigate an interactive environment while simultaneously performing structured programming reasoning. Existing UX frameworks have been developed predominantly for general entertainment contexts or non-game applications and therefore do not fully address the dual cognitive load inherent in programming-oriented RPGs. To address this gap, this research employs a qualitative approach combining expert validation, thematic synthesis, and the Fuzzy Delphi Method (FDM), involving ten experts from the fields of UX design, game development, and programming. The analysis yielded six empirically validated UX principles, namely Usability and Learnability, Accessibility and Readability, Responsiveness and Interaction Smoothness, Consistency and Predictability, Meaningful Feedback and Guidance, and Engagement Support. The defuzzified consensus values of these principles ranged from 0,59 to 0,72, with all six principles surpassing the acceptance threshold of 0,50, indicating sufficient expert agreement. Further analysis revealed that the six principles do not operate in isolation but form a network of interdependencies that can be represented as a three-layer hierarchical framework consisting of Foundation, Communication and Responsiveness, and Engagement. This study contributes by providing a specific, coherent, and empirically validated UX framework that can serve as a design and evaluation reference for programming-oriented Role-Playing Games.